Current Concepts for the Combined Treatment Modality of Ionizing Radiation with Anticancer Agents - Oehler, Christoph; Dickinson, Daniel J.; Broggini-Tenzer, Angela; Hofstetter, Barbara; Hollenstein, Andreas; Riesterer, Oliver; Vuong, Van; Pruschy, Martin (Current Pharmaceutical Design, 2007)
In current applied radiobiology, there exists a tremendous effort in basic and translational research to identify novel treatment modalities combining ionizing radiation with anticancer agents. This is mainly due to the highly improved molecular understanding of intrinsic radioresistance and the profiling of cellular stress responses to irradiation during recent years. Ionizing radiation not only damages DNA but also affects multiple cellular components that induce a multilayered stress response. The treatment responses can be restricted to the individual cell level but might also be part of an intercellular stress communication network. Both DNA damage-induced signaling (which results in cell cycle arrest and induction of the DNA-repair machinery) and also ionizing radiation-induced signal transduction cascades, which are generated at cellular sites distant from and independent of DNA-damage, represent interesting targets for anticancer treatment modalities to sensitize for ionizing radiation. Due to the lack of molecular knowledge classic radiobiology assembled the cellular and tissue responses into four groups (4 R's of radiotherapy) which describe biological factors influencing the treatment response to fractionated radiotherapy. These classic 4 R's are Repair, Reassortment, Repopulation and Reoxygenation. With the tremendous progress in molecular oncology we now begin to understand theses factors on the molecular level. At the same time this classification may guide modern molecular radiobiologists to identify novel pharmaceuticals and antisignaling agents which can modulate the treatment response to irradiation. In this review we describe current approaches to sensitize tumor cells with novel anticancer agents along the lines of these 4 R's.
Keywords: Reoxygenation